2016
DOI: 10.1124/jpet.116.238048
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 Reduces UVA-Mediated MMP-1 Upregulation via MAPK/AP-1 Signaling Cascades: The Photoprotective Effects of Sulforaphane and Hispidulin

Abstract: UVA irradiation plays a role in premature aging of the skin through triggering oxidative stress-associated stimulation of matrix metalloproteinase-1 (MMP-1) responsible for collagen degradation, a hallmark of photoaged skin. Compounds that can activate nuclear factor E2-related factor 2 (Nrf2), a transcription factor regulating antioxidant gene expression, should therefore serve as effective antiphotoaging agents. We investigated whether genetic silencing of Nrf2 could relieve UVA-mediated MMP-1 upregulation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 52 publications
(80 reference statements)
4
89
0
Order By: Relevance
“…Considering that NF‐κB partially upregulates MMP‐1 and ‐9 (Fanjul‐Fernandez, Folgueras, Cabrera, & Lopez‐Otin, ), resveratrol could exert anti‐wrinkle effect through activation of Nrf2 signaling pathway which antagonizes NF‐κB signaling. In addition, it is worthwhile to study the crosstalk between AP1 and Nrf2 signaling pathway to better understand the anti‐wrinkle mechanism of Nrf2 activators as the transcriptional regulation of MMP‐1 is mediated by activation of activator protein‐1 (AP‐1) and its upstream mitogen‐activated protein kinase signaling pathway (Chaiprasongsuk et al., ). Currently existing evidence also suggest that resveratrol behaves as an inhibitor of inflammation which is associated with photoaging and wrinkle formation (Kundu, Shin, & Surh, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that NF‐κB partially upregulates MMP‐1 and ‐9 (Fanjul‐Fernandez, Folgueras, Cabrera, & Lopez‐Otin, ), resveratrol could exert anti‐wrinkle effect through activation of Nrf2 signaling pathway which antagonizes NF‐κB signaling. In addition, it is worthwhile to study the crosstalk between AP1 and Nrf2 signaling pathway to better understand the anti‐wrinkle mechanism of Nrf2 activators as the transcriptional regulation of MMP‐1 is mediated by activation of activator protein‐1 (AP‐1) and its upstream mitogen‐activated protein kinase signaling pathway (Chaiprasongsuk et al., ). Currently existing evidence also suggest that resveratrol behaves as an inhibitor of inflammation which is associated with photoaging and wrinkle formation (Kundu, Shin, & Surh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not clear yet how Nrf2 and MMPs are regulated in opposite ways, Nrf2 suppresses the upregulation of MMPs most presumably by scavenging ROS (Chaiprasongsuk et al, 2017). In addition, NF-κB/p65 was reported to antagonize Nrf2 signaling pathway by depriving CREB binding protein (CBP) from Nrf2 (Liu, Qu, & Shen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the extracts of the APF22 and its components provided inhibitory effects on UVA-stimulated matrix metalloproteinase-1 (MMP-1) in correlation to their antioxidant actions in keratinocyte HaCaT cells . Moreover, GA (Panich, Onkoksoong, Limsaengurai, Akarasereenont, & Wongkajornsilp, 2012), FA, quercetin (Chaiprasongsuk, Onkoksoong, Pluemsamran, Limsaengurai, & Panich, 2016), and hispidulin (Chaiprasongsuk et al, 2017), which could be active constituents isolated from the APF22 formula, were demonstrated to have abilities to suppress UVA-induced melanogenesis in our previous in vitro and in vivo studies.…”
mentioning
confidence: 84%
“…Regarding the response to intracellular ROS generation, the Nrf2 is a key transcription factor activated in response to alterations in cell redox status, which promotes expression of several genes related to antioxidant defence mechanisms . Therefore, cosmetic products that trigger this pathway activation are considered promising as protective against photoageing and UVA‐induced skin damage processes . In the present study, sucupira NE did not modulate this pathway, although a significant decrease of intracellular oxidative stress was observed in NE treated groups (Figure ).…”
Section: Discussionmentioning
confidence: 45%
“…[47,48] Therefore, cosmetic products that trigger this pathway activation are considered promising as protective against photoageing and UVA-induced skin damage processes. [49,50] In the present study, sucupira NE did not modulate this pathway, although a significant decrease of intracellular oxidative stress was observed in NE treated groups (Figure 8). We thus hypothesize that this effect is associated with direct ROS neutralization by sucupira oil phytoconstituents, as already reported by other authors.…”
Section: Figure 7 Intracellular Formation Of Reactive Oxygen Species mentioning
confidence: 42%